Smith, Christopher. (2016). Los etruscos. Una breve aproximación. Madrid: Alianza. ISBN: 978-84-910-4305-8, 216 páginas. - Carpenito, Hernán (2018)
Fil: Carpenito, Hernán. Instituto Superior del Profesorado Dr. Joaquín V. González; Argentina